The perception of trade US & UK employess on the effectiveness of Scope International’s disaster recovery plan / Nur Ezlin Mohamed Ibrahim - Mohamed Ibrahim, Nur Ezlin (2011)
This thesis elaborates on the perception of employees in a private sector bank on the effectiveness of Disaster Recovery Planning. In this study, there were 4 variables choose by researcher. Effectiveness of Disaster Recovery Planning is the dependant variable while awareness of employees, technology and planning & preparation are selected to be independent variables for this research. This research used primary data which gathered from Scope International (M) Sdn Bhd then produced using SPSS for correlation analysis. The result then has been analyzed to see whether there are correlation between the dependant and independent variables or not. The study found that Awareness and Technology has no significant relationship and however shows positive impact towards the perception towards Disaster Recovery Planning. Meanwhile Proper planning and preparation shows significant.